Faculty Development Program in Nepalese Medical Schools: Past, Present, and Future Perspectives - Dhakal, Ajaya Kumar; Adhikari, Ramesh Kant (Journal of Nepal Health Research Council, 2023)
Teaching medical students is an art that requires expertise in the core content of the subject and specialized teaching techniques. Learning to teach medical students and teachers learning from those teachings themselves is a lifelong process. Short medical teacher training courses in various specialized teaching techniques lay the foundation for a positive teaching experience that can substantially impact medical education. The Faculty Development Program is one such training course for medical teachers, designed to be an essential step toward becoming a student-centered facilitator. This article sheds light on the current status and significance of the faculty development program in Nepalese medical education. It also offers suggestions and critical strategies to improve the program in the future with available resources and to integrate it further into medical education. Keywords: Faculty development program; medical education; Nepal; teacher training